Intelligent artificial limb arm control method based on vitality interface - YAO JIE; ZHANG BI; XU ZHUANG; ZHAO MING; ZHAO XINGANG; LI JIWEI (2022)
The invention particularly relates to an intelligent artificial limb arm control method based on a vitality interface. Comprising the following steps: an intention recognition stage: collecting sEMG signals of a subject in a hand or elbow movement process, performing muscle collaborative extraction, and predicting a corresponding hand action or elbow movement result through model mapping calculation; a task analysis stage: collecting a group of sEMG signals in the hand or elbow movement process, respectively judging the myoelectricity data quality of the current patient, correcting the expected input, and obtaining the corrected expected input; and a coordination control stage: performing control task calculation on the corrected expected input, and finally performing corresponding bottom layer control to complete the complete control process of the intelligent artificial limb. The sEMG signals of the upper arm of the affected side of the disabled and the muscle of the stump part are used for recognizing the